2020
DOI: 10.3389/fpsyg.2020.00878
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Orthography on Text Production in Three Languages: Catalan, English, and Spanish

Abstract: Learning to write effectively is key for learning and participation in social communities. In English, transcription skills (handwriting and spelling) constrain written production at the early stages of learning to write. The effect of transcription diminishes with age, when reading skills enhance text production. Less is known about how transcription and reading interact with writing in other languages. In this study, we explore the relationships between spelling, reading and the length and quality of written… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
(74 reference statements)
2
7
0
Order By: Relevance
“…This was rather an incidental finding as the focus of the present study was really on spelling errors. Future studies may want to further investigate the nature of the differences observed in the present study, including predictors of different components of text spelling such as morphological awareness (e.g., in Desrochers et al, 2018) but also reading and transcription skills involved at different stages of the development of text production (Llaurado and Dockrell, 2020). We also suggest that reading might be a better indicator of phonological skills in late primary school than an explicit measure of phonological awareness.…”
Section: Underlying Processes In French and English Spelling Developmmentioning
confidence: 73%
“…This was rather an incidental finding as the focus of the present study was really on spelling errors. Future studies may want to further investigate the nature of the differences observed in the present study, including predictors of different components of text spelling such as morphological awareness (e.g., in Desrochers et al, 2018) but also reading and transcription skills involved at different stages of the development of text production (Llaurado and Dockrell, 2020). We also suggest that reading might be a better indicator of phonological skills in late primary school than an explicit measure of phonological awareness.…”
Section: Underlying Processes In French and English Spelling Developmmentioning
confidence: 73%
“…The full administration procedure lasted for 50 min. This is the typical duration of writing tasks in the participating schools, also used in prior studies (e.g., Llaurado and Dockrell, 2020 ). The exact same procedure was followed for both cohorts and testing moments.…”
Section: Methodsmentioning
confidence: 99%
“…In the word level, spelling could be defined as the ability to retrieve, assemble, and select orthographic symbols (Abbott and Berninger, 1993 ). Large-span cross-sectional studies found that spelling errors (an indicator of spelling skill) decreased throughout schooling, for example, from Grades 2 to 5 (Alves and Limpo, 2015 ), Grades 2 to 6 (Llaurado and Dockrell, 2020 ; Magalhães et al, 2020 ), and Grades 1 to 9 (Bahr et al, 2012 ). However, a few studies examined the type of errors produced, which can inform about the spelling difficulties of students in each language.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy may be affected by features of the language used. For example, fewer spelling errors are observed in transparent than in opaque languages (for a comparison between Spanish and English, see Llaurado & Dockrell, 2020). Complexity measures assess lexical usage and syntactic structures, generally at the sentence, clause, or word level (or in T‐units; e.g., the number of clauses per T‐unit).…”
Section: Writing Research Across Languagesmentioning
confidence: 99%